Analisis Kesulitan Belajar Matematika Siswa Kelas V pada Materi KPK dan FPB Madrasah Ibtidaiyah Negeri 2 Kota Palembang - Tiara Ariska (el-Ibtidaiy:Journal of Primary Education, 2020)
This research aims to desrible the location of the difficulty students in learning mathematics in the material KPK and FPB. The studiwas conducted at MIN 2 Palembang subject main this research is a fifth grade student which numbered 40 people student. Type of apporoach in research this is qualitative and duantitative approache, data collection methods used is written test method observation and interview. Fromthe final result data obtained 40 % students who have difficulty 45 % understand the material and 15 % moderate students. Internal factors and external factors, internal factors are the lack of attetntion when yhe teacher explains the material of KPK and FPB the difficulty of doing quentions in the form of stories one the KPK material and the lack interest in learning they undertand mathematics. Ekternal factors stem from their lack of understanding of the method used.